Trial of the Primary Care Practice Improvement Tool: building organisational performance in Australian general practice and primary health care. (18th April 2016) - Crossland, Lisa; Upham, Susan J; Janamian, Tina; Siskind, Victor; Sheehan, Mary; Jackson, Claire L
Abstract: Objective: To nationally trial the Primary Care Practice Improvement Tool (PC‐PIT), an organisational performance improvement tool previously co‐created with Australian primary care practices to increase their focus on relevant quality improvement (QI) activities. Design: The study was conducted from March to December 2015 with volunteer general practices from a range of Australian primary care settings. We used a mixed‐methods approach in two parts. Part 1 involved staff in Australian primary care practices assessing how they perceived their practice met (or did not meet) each of the 13 PC‐PIT elements of high‐performing practices, using a 1–5 Likert scale. In Part 2, two external raters conducted an independent practice visit to independently and objectively assess the subjective practice assessment from Part 1 against objective indicators for the 13 elements, using the same 1–5 Likert scale. Concordance between the raters was determined by comparing their ratings. In‐depth interviews conducted during the independent practice visits explored practice managers' experiences and perceived support and resource needs to undertake organisational improvement in practice. Results: Data were available for 34 general practices participating in Part 1. For Part 2, independent practice visits and the inter‐rater comparison were conducted for a purposeful sample of 19 of the 34 practices. Overall concordance between the two raters for each of the assessed elements was excellent. Three practice types across a continuum of higher‐ to lower‐scoring practices were identified, with each using the PC‐PIT in a unique way. During the in‐depth interviews, practice managers identified benefits of having additional QI tools that relate to the PC‐PIT elements. Conclusions: The PC‐PIT is an organisational performance tool that is acceptable, valid and relevant to our range of partners and the end users (general practices). Work is continuing with our partners and end users to embed the PC‐PIT in existing organisational improvement programs.